Strengthening Non-Formal Education Through Study Groups In Pagar Merbau I Village - Dina Sri Novita; Mutiara Rahmah; Nurul Haliza Lubis; Silvia; Wardah Tulail Nadila; Dalimunthe, Gabena Indrayani (Yayasan Salam Cerdas Al-Fattah, 2024)
This study examines the strengthening of non-formal education through study groups in Pagar Merbau I Village. The results of the study show that learning groups have a significant role in increasing access to education for the community, especially in remote areas. Through the programs held, the study group succeeded in increasing skills, knowledge, and educational awareness among villagers. In addition, the study group is also able to encourage active participation of the community in the educational process, both as participants and organizers of activities. These findings emphasize the importance of collaboration between the government, the community, and other related parties in strengthening non-formal education as an effort to equalize access to education in rural areas. This study recommends the development of sustainable strategies to support the sustainability of study groups in order to realize a more educated, independent, and competitive society